Faktor Risiko yang Berpengaruh Terhadap Status Kontrol Glikemik pada Kehamilan dengan Diabetes Melitus (Studi Kasus Kontrol Pasien di Beberapa RS di Kota Semarang) - Resna Meiwarnis; Ariawan Soejoenoes; Heri Nugroho; Suharyo Hadisaputro; Henry Setyawan (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2016)
Background : The number of diabetes patients was higher in women than men. The high prevalence in women occurs in pregnant women because of the increasing age of childbearing. Commonly, pregnancy in women with diabetes was associated with morbidity and mortality. Data obtained from Diabetic Department King’s College Hospital mentioned that during pregnancy, a good control of maternal diabetes cause a progressive decline in blood glucose control. The purpose of this research is to explain some risk factors related to glycaemic control status in pregnancy with diabetes mellitus. Methods : This research was an observational study using case control design by using retrospective approach. The population of this study is all cases of pregnancy with diabetes with the number of sample was 62 people, consist of 31 cases and 31 control with consecutive sampling. In this research, cases sample selection was chosed from pregnant women with diabetes who come to Tugurejo Hospital, Semarang City Hospital and Roemani Hospital during 2015. Control sample selection was chosed from non pregnant women with diabetes who come to Tugurejo Hospital, Semarang City Hospital and Roemani Hospital during 2015. Results : The pattern of taking medications that was not good (p= 0,002; aOR= 7,2; 95%CI= 1,9-17,2) was risk factors of poor glycaemic control status with probability event amounted was 70,0%. Conclusion : The risk factors to glycaemic control status in pregnancy with diabetes was the pattern of taking medications that was not good. Background :Thenumber ofdiabetes patients washigher inwomen thanmen.Thehigh prevalence in women occurs in pregnant women because of the increasing age of childbearing. Commonly, pregnancy inwomen withdiabetes wasassociated withmorbidity andmortality. Dataobtained fromDiabetic Department King’s College Hospital mentioned that during pregnancy, agood control ofmaternal diabetes cause aprogressive decline in bloodglucosecontrol.Thepurposeof thisresearchisto explainsomeriskfactorsrelatedto glycaemiccontrolstatusinpregnancywithdiabetesmellitus.Methods :Thisresearch wasanobservational studyusingcasecontrol design by using a retrospective approach. Thepopulation ofthisstudyisallcasesofpregnancy withdiabetes with the number of sample was 62 people, consist of 31 cases and 31 control with consecutive sampling. In this research, cases sample selection was chosed from pregnant women with diabetes who come to Tugurejo Hospital, Semarang City Hospital and Roemani Hospital during 2015. Control sample selection was chosed from non pregnant women with diabetes who come to Tugurejo Hospital, Semarang City Hospital and RoemaniHospitalduring2015.Results:Thepatternoftakingmedications thatwasnotgood(p=0,002;aOR=7,2;95% CI=1,9-17,2)was risk factors of poor glycaemic control status with probability event amountedwas70,0%.Conclusion :Theriskfactorstoglycaemiccontrolstatusinpregnancywithdiabeteswasthe patternoftakingmedicationsthatwasnotgood.